Determinasi Faktor Psikologis dan Perilaku dalam Penggunaan ATM untuk Transaksi Pembayaran di Indonesia - Nindia Nur Arifiana Putri; Yeni Tata Rini (Jurnal of Management and Social Sciences, 2026)
Abstract. This study aims to analyze the psychological and behavioral factors that influence ATM usage for payment transactions in Indonesia. This study used a quantitative approach with an explanatory design, involving customer respondents aged 18 years and over who had experience using ATMs. Data were collected via questionnaire and analyzed using statistical tests including normality, correlation, and paired sample tests. The variables studied included perceived usefulness, perceived ease of use, attitude, subjective norm, perceived behavioral control, perceived risk, intention usage, and behavior usage. The results showed that all psychological variables significantly influenced intention usage, which in turn significantly influenced ATM usage behavior. Furthermore, perceived risk was found to be an important factor that can hinder the realization of intention into actual behavior. This study also indicated the existence of an intention-behavior gap, where not all intentions to use ATMs are realized into actions. The conclusion of this study confirms that the integration of the TAM, TPB, and perceived risk models provides a more comprehensive understanding of ATM usage behavior. This study contributes theoretically to the development of technology behavior models and practically to the banking industry in designing strategies to increase ATM usage. Keywords: Perceived Usefulness; Perceived Ease of Use; Theory of Planned Behavior; Perceived Risk; Intention Usage; Behavior Usage; ATM; Banking Consumer Behavior